2D IMAGE-BASED INDUSTRIAL ROBOT END EFFECTOR TRAJECTORY CONTROL ALGORITHM - CZARNECKA, Anna; SOBASZEK, Łukasz; ŚWIĆ, Antoni (Applied Computer Science, 2018)
This paper presents an algorithm for programming an industrial robot’s end effector path based on 2D images. The first section gives a brief overview of modern solutions for industrial robot implementation. The next section describes the test set-up and the software used in tests. The work also presents the key elements of the controller algorithm and their operation: 2D image processing with MATLAB software, generating the code for robot control in AS language, and implementation of the produced codes to the Kawasaki RS003N robot.